Physics, asked by sssbabu1970, 11 months ago

On the moon's surface , the acceleration due to gravity is 1.67 m/s^2 . If the radius of the moon is 1.74 * 10^6 m . Calculate the mass ( G = 6.67 * 10^11 Nm^2 / kg^2 ).


pls make it fast pls..........very urgent

Answers

Answered by ERB
32

Answer:

7.58 × 10²² Kg

Explanation:

a= \frac{GM}{R^2}

M= \frac{aR^2}{G} = \frac{ 1.67 \times (1.74 \times 10^6)^2}{6.67 * 10^{-11}} = 7.58 × 10²² Kg

Answered by Anonymous
104

\red{\large\underline{\underline\mathtt{To\:Find:}}}

The mass of the "Moon"..

\blue{\large\underline{\underline\mathtt{Given:}}}

  • Acceleration due to gravity : 1.67ms^{-2}

  • Radius of Moon = 1.74 \times 10^{6}m

  • G = 6.67 \times 10^{-11}

\purple{\Large\underline{\underline\mathtt{We\:know:}}}

☆ We know the relation ,

\purple{\sf{\boxed{g = \dfrac{GM}{R^{2}}}}}

☞ Where ,

  • g = Acceleration due to gravity

  • G = Universal Gravitational constant

  • R = Distance

\red{\Large\underline{\underline\mathtt{Concept:}}}

From the formula , we can get a exact equation to find out mass of Moon or simply substituting the value in the Formula .........

\green{\Large\underline{\underline\mathtt{Solution:}}}

☯ From the relation,

\purple{\sf{g = \dfrac{GM}{R^{2}}}}

☯ we get ,

\purple{\sf{M = \dfrac{gR^{2}}{G}}}

Substituting the values in it we get,

\mathtt{\Rightarrow M = \dfrac{\left(1.74 \times 10^{6}\right)^{2} \times 1.67}{6.67 \times 10^{-11}}}

\mathtt{\Rightarrow M = \dfrac{1.74 \times 1.74 \times 10^{12} \times 1.67}{6.67 \times 10^{-11}}}

\mathtt{\Rightarrow M = \dfrac{5.05 \times 10^{12}}{6.67 \times 10^{-11}}}

\mathtt{\Rightarrow M = \dfrac{5.05 \times 10^{23}}{6.67}}

\mathtt{\Rightarrow M = \dfrac{\cancel{5.05} \times 10^{23}}{\cancel{6.67}}}

\mathtt{\Rightarrow M = 0.75 \times 10^{23}}

\mathtt{\Rightarrow M = 7.5 \times 10^{22} kg}

{\boxed{\therefore Mass = 7.5 \times 10^{22} kg}}

\red{\large\underline{\underline\mathtt{Extra\:Information:}}}

║Some Formulas related to Gravitation║

  • Newton's Universal Law of Gravitation

\mathtt{F = G\dfrac{m_{1}m_{2}}{d^{2}}}

or,

\mathtt{G = \dfrac{Fd^{2}}{m_{1}m_{2}}}

  • Equations of motion for free falling body..

\mathtt{v = u + gt}

\mathtt{h = ut + \dfrac{1}{2}gt^{2}}

\mathtt{v^{2} = u^{2} + gh}

✪ Where,

  • v = final velocity
  • u = initial velocity
  • t = time taken
  • g = acceleration due to gravity
  • h = height

______________________________________

Similar questions